2015
DOI: 10.1186/s40591-015-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Outlook on PI3K/AKT/mTOR inhibition in acute leukemia

Abstract: Technological advances allowing high throughput analyses across numerous cancer tissues have allowed much progress in understanding complex cellular signaling. In the future, the genetic landscape in cancer may have more clinical relevance than diagnosis based on tumor origin. This progress has emphasized PI3K/AKT/mTOR, among others, as a central signaling center of cancer development due to its governing control in cellular growth, survival, and metabolism. The discovery of high frequencies of mutations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 126 publications
(153 reference statements)
1
109
0
1
Order By: Relevance
“…In AML, mTOR activation is seen in nearly all AML cases, as is phosphorylation of downstream targets such as p70S6, S6RP, and 4EBP1. [53][54][55] Clinical data suggest that mTOR inhibitors have potential therapeutic roles in a number of hematologic malignancies, including acute lymphoblastic leukemia, chronic myelogenous leukemia, mantle cell lymphoma, anaplastic large-cell lymphoma, and lymphoproliferative disorders. 56 All of these studies reveal that targeting mTORcentered autophagy may have broad therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In AML, mTOR activation is seen in nearly all AML cases, as is phosphorylation of downstream targets such as p70S6, S6RP, and 4EBP1. [53][54][55] Clinical data suggest that mTOR inhibitors have potential therapeutic roles in a number of hematologic malignancies, including acute lymphoblastic leukemia, chronic myelogenous leukemia, mantle cell lymphoma, anaplastic large-cell lymphoma, and lymphoproliferative disorders. 56 All of these studies reveal that targeting mTORcentered autophagy may have broad therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-AKT-mTOR pathway is hyperactive in patient-derived AML cells. However, rapamycin and its analogs failed to provide a significant improvement of response in leukemia patients [87], most likely due to the negative feedback loops. The elevation of RTK-PI3K-PDK1 activity in response to rapamycin can promote Akt phosphorylation on Thr308, which may be sufficient for cell survival [88].…”
Section: Targeting Mtor Signaling For Leukemia Therapymentioning
confidence: 99%
“…Torin-2, an ATP-competitive inhibitor of mTOR, causes both apoptosis and autophagy and suppresses the cell cycle by affecting both mTORC1 and mTORC2 activities [93,95]. However, no clinical data for TOR-KIs have been reported thus far [87]. The compounds NVP-BEZ235 and XL-765 (Exelixis) simultaneously inhibit PI3K and mTOR kinases and decrease the phosphorylation of Akt, S6K1, and 4E-BP1.…”
Section: Targeting Mtor Signaling For Leukemia Therapymentioning
confidence: 99%
“…Fransecky et al reviewed the preclinical and clinical trials of these aforementioned inhibitors in AML, B-ALL, B-CLL, T-ALL, non-Hodgkin lymphoma (NHL), and MDS, but found that the clinical trial data are rather disappointing (73). In addition to the four main inhibitors that targeting the PI3K/Akt/mTOR signaling pathway, many other inhibitors are also in development.…”
Section: Inhibitors Targeting Pi3k/akt/mtor Signaling Pathway For Hemmentioning
confidence: 99%